Kostnadseffektiv svaveldioxidreduktion - Karlsson, Linda (2007)
In Sweden the work of reducing acidification and its prime cause; emission and deposition of sulphur dioxide, has been going on for decades. Despite of all the work that has been done the positive progress in the acidified areas is slow. This is partly due to a long recovery time for the acidified areas but also because the reductions of emission and deposition of sulphur dioxide have not been large enough.